Analisis Yuridis Penyelesaian Tindak Pidana Penggelapan Melalui Pendekatan Keadilan Restoratif (Restoratif Justice)(Studi Putusan Pengadilan Negeri Tanjung Selor Nomor 39/Pid.B/2022/Pn Tjs) - Chairuddin Lubis; Syahrul Bakti Harahap (Albayan Journal of Islam and Muslim Societies, 2024)
Criminal law practice, which initially emphasized retributive justice, is shifting toward restorative justice, focusing on restoring relationships among victims, offenders, and society. This study examines the legal framework and mechanisms for applying restorative justice under Indonesian law, particularly in embezzlement cases through the District Court Decision of Tanjung Selor No. 39/Pid.B/2022/PN.Tjs. The research is descriptive with a normative juridical approach and qualitative analysis. Findings indicate that restorative justice is regulated under Supreme Court Regulation No. 1 of 2024, emphasizing dialogue, mediation, and reconciliation to achieve fair settlements. In the embezzlement case, the defendant directly apologized to the victim, expressed remorse, and accepted responsibility. The judge’s consideration focused on recovery, resulting in a five-month prison sentence, lighter than the prosecutor’s demand. The study concludes that restorative justice provides a faster, simpler, fairer resolution while reducing the burden on the judicial system. It is recommended that the legal substance of restorative justice be further strengthened and law enforcement officers optimize its implementation by involving community participation and legal culture.